The transformative potential of intersecting arts-based inquiry and environmental learning in urban South Africa: a focus on socio-ecological water pedagogies - James, Anna Katharine (Rhodes University, Faculty of Education, Department of Education)
In this study I explore and explain transformative potential in arts-based environmental learning with a focus on water pedagogy. The study took place over a period of four years, where approximately 40 school pupils between the ages of 10 and 17 years-old were engaged in participatory arts-based inquiries into water located across unequal neighbourhoods in Cape Town, South Africa. Educators, school learners, citizens and decision-makers hold different historical, cultural, political and spiritual perspectives on water. These play a role in shaping what is termed in this research the 'hydro-social cycle'. Yet, due to dominant ideas of what counts as knowing and truth, educators in educational settings struggle to account for the complexity of water, limiting educational encounters to a partial knowing leading mostly to limited unimaginative framings of problems and solutions. My focus on transformative potential in learning is derived from a concern for how environmental education encounters and the sense-making they enable, are infused by socio-economic, political, and historical elements, specifically colonialism, capitalism, and white supremacist racism. The connections between the multiple layers of capitalist crisis and the ever-urgent environmental crisis are not adequately made in mainstream forms of water education. The research explores how arts-based pedagogy could enable a productive meeting of critical environmental education with ecological literacies. Within this positioning, transformative potential considers how educational engagements position questions about water within the social life of participants/learners and inform learning that leads to fuller and more nuanced greater knowledge. Theoretically, I work with an interrogation of critical education theory, underlaboured by critical realism which enabled me to rigorously consider how claims to knowing are shaped by their accompanying assumptions of what is real. Drawing on recent debates in critical education theory, I resist the notion of critique as ideology and engage instead in the craftsmanship of contextual and responsive inquiry practice. This has enabled me to articulate processes and relationships in water education encounters with meaningful understandings of the effects of simultaneous crises rooted in racial capitalism and environmental crisis. My methodological approach is arts-based educational research with a directive to reflect upon educational encounters in an integrated way. It includes two parts informing the facilitation and analysis of open-ended learning processes. One component was arts-based inquiry practice developed for exploring complexity, drawing on the thinking of Norris (2009, 2011) and Finley (2016, 2017). The second part holds reflective space for these encounters guided by the practice of pedagogical narration inspired by the Reggio Amelia approach, demonstrated by Pacini-Ketchabaw, Nxumalo, Kocher, Elliot and Sanchez (2014). Clarifying the intellectual work of a responsive educator-researcher, pedagogical narration brings multiple theoretical lenses into conversation with emergent dimensions of educational process. In practice, in order to transgress the dominance of colonial white supremacist knowledge frames of water, I needed to be curious, to be confounded, to expect the unexpected in the educational encounters with participants and this mirroring of practice was emulated by the participants as they followed their own questions about water in Mzansi (South Africa). In our work together we came up against assumptions we had previously not questioned as individuals. Together we explored the implications of this by, for example, questioning who is responsible for saving water. These explorations required bringing together science knowledge and everyday knowledge at multiple scales: the household, catchment, government and global. It required us to be critical of how language and images are mobilized in public communication and school curriculums; for example, representations of water are infused with history and power in a way that impacts how we know and teach about water. The transformative potential of this pedagogical space is generated through acts of creative expression which are seen as acts of absenting absence, for example exhibiting through play how water use in the household interconnects with gender and age relationships. As such, creative expression through multiple mediums or more-than-text enables a deeper understanding of water as well as openings for interdisciplinary engagement with learning about water. My research found that in bringing together the contributions of critical education and environmental education in practice, two shifts are needed: environmental educators need to view ecological literacy as inseparable from the social and political. The knowledge that is shared about water in the classroom has social and political implications. On the other hand, critical educators need to better locate justice concerns in the material and ecological world at scale. Arts-based inquiry, as a kind of scaffolding for pedagogical process, has the potential to enable these shifts by opening up fixed analytical frames. Making these shifts requires a reflective practice on the part of the educator to navigate the inherited blind spots in environmental learning and critical education, such as dualities. One way to do this is for the educator to identify absences, as articulated in the Critical Realist tradition, and consider how these absences might be absented. This differs from a simplistic process of critique in the possibilities it opens up for collaboration between different schools of thought rather than further polarisation and alienation between educators and knowledge keepers on social ecologies. These insights have relevance for many sites of environmental education practice, such as natural science lecturers, school teachers or community activists. It is knowledge-learning work emergent from and responsive to complex ecological crisis, which requires everyone to rethink and open up to new ways of being, seeing and doing around these issues. The transformative potential of this work is that the thinking and transforming at all scales can be catalysed and grounded through the arts based educational encounters with the participants.
Keywords: Environmental education -- South Africa; Water conservation-- Study and teaching -- South Africa; Art in environmental education -- South Africa; Social learning -- South Africa; Educational sociology -- South Africa; Water-supply Social aspects -- South Africa; Critical realism; Socio-ecological education